2013
DOI: 10.1593/tlo.12448
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Primary and Metastatic Liver Tumors

Abstract: SBRT provides excellent local control for both primary and metastatic liver lesions with minimal toxicity. Future studies should focus on appropriate selection of patients and on careful assessment of liver function to maximize both the safety and efficacy of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…SBRT has the ability to concentrate the radiation dose to a confined anatomical area over a shorter number of fractions and to minimize adjacent toxicities. Our center has been a forerunner in the use of SBRT for a variety of hepatic malignancies, and it has been shown to be safe and effective, even in the presence of underlying liver disease . Therefore, we sought to build on this experience by using a combination of SBRT (in 5 fractions or fewer) and subsequent oral capecitabine for the neoadjuvant treatment of patients with unresectable hilar CCA before transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SBRT has the ability to concentrate the radiation dose to a confined anatomical area over a shorter number of fractions and to minimize adjacent toxicities. Our center has been a forerunner in the use of SBRT for a variety of hepatic malignancies, and it has been shown to be safe and effective, even in the presence of underlying liver disease . Therefore, we sought to build on this experience by using a combination of SBRT (in 5 fractions or fewer) and subsequent oral capecitabine for the neoadjuvant treatment of patients with unresectable hilar CCA before transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…After radiation therapy, chemotherapy has traditionally been based on a 5‐fluorouracil infusion followed by capecitabine. Our center has developed the novel use of stereotactic body radiation therapy (SBRT) in the treatment of hepatic malignancies . Safety and efficacy have been demonstrated for these cancers often in many patients with underlying liver disease or cirrhosis .…”
mentioning
confidence: 99%
“…[3,10] Stereotactic body radiation therapy (SBRT) is becoming an emerging and effective treatment paradigm in radiation therapy to treat early stage non-small cell lung cancer and liver cancer patients with promising early clinical outcome. [6,14,16,17] Compared to traditional fractionated radiotherapy, SBRT delivers much higher radiation dose per fraction in one to five fractions. On-board 4D or real time volumetric verification of the target location before and during the treatment is critical for lung and liver SBRT treatments due to its tight PTV margin, high fractional dose and long treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the past 10 years have demonstrated that SBRT can safely and effectively treat liver tumors up to 6 cm in size with local control rates higher than 80% to 90%. [9][10][11][12][13][14][15][16] The treatment of liver tumors with SBRT, however, is often limited by liver dose constraints aimed at minimizing the risk of radiation-induced liver disease (RILD). It is generally accepted in the surgical literature that 75% to 80% of a 2000-mL noncirrhotic liver can be safely resected.…”
Section: Introductionmentioning
confidence: 99%